Given that
a + b + c = 1
a 2 + b 2 + c 2 = 2
a 3 + b 3 + c 3 = 3
Then a 4 + b 4 + c 4 = a 2 a 1 .... where a 1 and a 2 are positive coprime integers.
And a 5 + b 5 + c 5 = a 3 ...... where a 3 is an integer.
And a 6 + b 6 + c 6 = a 5 a 4 ....where a 4 and a 5 are positive coprime integers.
And a 7 + b 7 + c 7 = a 7 a 6 ....where a 6 and a 7 are positive coprime integers.
And a 8 + b 8 + c 8 = a 9 a 8 ... where a 8 and a 9 are positive coprime integers.
Find a 1 + a 2 + a 3 + a 4 + a 5 + a 6 + a 7 + a 8 + a 9 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using Newton's Identity...
But since the polynomial is of third-degree polynomial, there are 4 terms and since there are 4 terms, there are 4 numerical coefficients, so for a(n-k) = 0 for k greater than or equal to 4.
This reduces to a(n)S(7) + a(n-1)S(6) + a(n-2)S(5) + a(n-3)S(4) = 0 where from earlier, we assumed that a(n) = 1, so a(n-1) = -1, a(n-2) = -1/2, and a(n-3) = -1/6.
Where we assume that a(n) = leading coefficient of polynomial = 1 of a(3)x^3 + a(2)x^2 + a(1)x + a(0) = P(x).
After algebraic manipulations, we get that S(8) = 1265/72 and from earlier, S(7) = 221/18, S(6) = 103/12, S(5) = 6, and S(4) = 25/6. Hence, the answer.
Yeah.. the line "This reduces to..." must start from a(n)S(8) + ... = 0.
U s i n g N e w t o n a n d n o t a t i o n s , f r o m t h e g i v e n d a t a : − P 1 = S 1 = 1 . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . P 1 = 1 P 2 = S 1 ∗ P 1 − 2 ∗ S 2 = 2 , s o . . . . . . S 2 = − 1 / 2 . . . . . . . . . . . . . . . . . . . . . . . P 2 = 2 P 3 = S 1 ∗ P 2 − S 2 ∗ P 1 + 3 ∗ S 3 ∗ = 3 , s o . . . . . . S 3 = 1 / 6 . . . . . . . . . . . . . . . . . . P 3 = 3 F o r G r e a t e r t h a n P 3 , P i = S 1 ∗ P i − 1 − S 2 ∗ P i − 2 + S 3 ∗ P i − 3 . S o f o r t h i s p r o b l e m P i = P i − 1 + 1 / 2 ∗ P i − 2 + 1 / 6 ∗ P i − 3 . ∴ P 4 = 3 + 1 / 2 ∗ 2 + 1 / 6 ∗ 1 = 2 5 / 6 = a 1 / a 2 , a 1 = 2 5 a 2 = 6 . P 5 = 2 5 / 6 + 1 / 2 ∗ 3 + 1 / 6 ∗ 3 = 6 = a 3 , a 3 = 6 . P 6 = 6 + 1 / 2 ∗ 2 5 / 6 + 1 / 6 ∗ 3 = 1 0 3 / 1 2 = a 4 / a 5 , a 4 = 1 0 3 a 5 = 1 2 . P 7 = 1 0 3 / 1 2 + 1 / 2 ∗ 6 + 1 / 6 ∗ 2 5 / 6 = 2 2 1 / 1 8 = a 6 / a 7 , a 6 = 2 2 1 a 7 = 1 8 . P 8 = 2 2 1 / 1 8 + 1 / 2 ∗ 1 0 3 / 1 2 + 1 / 6 ∗ 6 = 1 2 6 5 / 7 2 = a 4 − 8 / a 9 , a 8 = 1 2 6 5 a 9 = 7 2 . i = 1 ∑ 9 a i = 1 7 2 8 .
how?... ........
Problem Loading...
Note Loading...
Set Loading...
I always wanted to solve this systematically. Perhaps the following helps. I used Newton's sums.
Let P 1 = a + b + c , P 2 a 2 + b 2 + c 2 , P 3 = a 3 + b 3 + c 3 . . .
and S 1 = a + b + c , S 2 = a b + b c + c a and S 3 = a b c .
Then we have:
P 1 = S 1
P 2 = S 1 P 1 − 2 S 2
P 3 = S 1 P 2 − S 2 P 1 + 3 S 3
P 4 = S 1 P 3 − S 2 P 2 + S 3 P 1
P 5 = S 1 P 4 − S 2 P 3 + S 3 P 2
P 6 = S 1 P 5 − S 2 P 4 + S 3 P 3
P 7 = S 1 P 6 − S 2 P 5 + S 3 P 4
P 8 = S 1 P 7 − S 2 P 6 + S 3 P 5
Therefore,
P 1 = 1
2 = 1 − 2 S 2 ⇒ S 2 = − 2 1
3 = 2 + 2 1 + 3 S 3 ⇒ S 3 = 6 1
P 4 = 3 + 2 1 ( 2 ) + 6 1 ( 1 ) = 6 2 5
P 5 = 6 2 5 + 2 1 ( 3 ) + 6 1 ( 2 ) = 6
P 6 = 6 + 2 1 ( 6 2 5 ) + 6 1 ( 3 ) = 1 2 1 0 3
P 7 = 1 2 1 0 3 + 2 1 ( 6 ) + 6 1 ( 6 2 5 ) = 1 8 2 2 1
P 8 = 1 8 2 2 1 + 2 1 ( 1 2 1 0 3 ) + 6 1 ( 6 ) = 7 2 1 2 6 5
Therefore, a 1 + a 2 + a 3 + a 4 + a 5 + a 6 + a 7 + a 8 + a 9
= 2 5 + 6 + 6 + 1 0 3 + 1 2 + 2 2 1 + 1 8 + 1 2 6 5 + 7 2 = 1 7 2 8